1356. Improvement in Quality of Life for Adults With Acute Bacterial Skin and Skin Structure Infections Following Treatment With Omadacycline or Linezolid. (26th November 2018) - Tzanis, Evan; Chitra, Surya; Curran, Marla; McGovern, Paul; Hinahara, Jordan; Goss, Thomas
Abstract: Background: The appearance of multidrug-resistant Gram-positive bacteria is a major challenge in clinical care. Omadacycline is the first aminomethylcycline antibiotic (semisynthetic compounds related to tetracyclines) in late-stage clinical development for acute bacterial skin and skin structure infections (ABSSSI), and demonstrates potent in vitro activity against many pathogens. Methods: Seven hundred thirty-five patients were enrolled in the OASIS-2 randomized controlled trial comparing omadacycline and linezolid for the treatment of adult subjects with ABSSSI known or suspected to be due to a Gram-positive pathogen, with 368 and 367 enrolled in each group, respectively. Subjects completed the 36-Item Short Form Health Survey Version 2 (SF-36v2), a validated questionnaire on physical and mental health, at both screening and post-treatment evaluation. Results of the SF-36v2 were analyzed in accordance with established norm-based standards for the survey (Ware 2000) for the intention-to-treat population. Results: Subjects who received omadacycline experienced a 3.25 point mean improvement in overall physical health ( P < 0.001, Figure 1) and reported significant improvements across all but one component parameter of overall physical and mental health, including physical functioning, bodily pain, role physical, vitality, role emotional, mental health, and social functioning (Figure 2). In contrast, while overall physical health improved for subjects who received linezolid, the improvement in vitality, role emotional, mental health, and general health was not significant (Figure 2). Although omadacycline achieved greater increase from baseline than linezolid across all domains analyzed, the difference in scores was not statistically significant at the P < 0.05 level (Figure 1). Conclusion: Omadacycline provides significant improvement in the physical component of quality of life over baseline for adult subjects with ABSSSI known or suspected to be due to a Gram-positive pathogen. Although the OASIS-2 trial was neither designed nor powered to measure differences in quality of life following treatment, trends identified in this analysis merit further investigation. References 1. Ware JE. SF-36 Health Survey Update. SPINE 2000; 25(24); 3130–3139. Disclosures: E. Tzanis, Paratek Pharmaceuticals: Employee, Salary. M. Curran, Paratek Pharmaceuticals: Employee, Salary. P. McGovern, Paratek Pharmaceuticals: Employee, Salary. J. Hinahara, Paratek Pharmaceuticals: Consultant, Consulting fee. T. Goss, Paratek Pharmaceuticals: Consultant, Consulting fee.